Morphological regional differences of epithelial cells along the midgut in Diatraea saccharalis Fabricius (Lepidoptera: Crambidae) larvae - Pinheiro, Daniela O. [UNESP]; Quagio-Grassiotto, Irani [UNESP]; Gregorio, Elisa A. [UNESP] (Entomological Soc Brasil, 2008)
The sugarcane borer, Diatraea saccharalis Fabricius, is a pest to sugarcane and many other crops. This work aims to characterize morphological variability in the epithelial cells (columnar, goblet and regenerative) along the midgut of D. saccharalis larvae. Fragments of the midgut (anterior, middle and posterior regions) were fixed and processed by light and scanning electron microscopy. There are both cytochemical and ultrastructural differences in the morphology of the epithelial cells, depending on their localization along the midgut. The apical surface of columnar cells shows an increase in both number and size of the apical protrusions from the anterior to the posterior midgut regions. There is an increase in the amount of PAS-positive (Periodic Acid-Schiff Reaction) granules detected in the cytoplasm of both the columnar and regenerative cells, from the anterior to the posterior region. The goblet cell apical surface is narrow in the anterior region, and enlarged in the posterior midgut; the chamber's cytoplasm extrusion are small and thin at the apical cavity surface, being thicker, longer and more numerous at the basal portion of the cavity. Our results suggest that the sugarcane borer midgut has two morphologically different regions, the anterior and the posterior; the middle region is a transitional region.

A broca da cana, Diatraea saccharalis Fabricius, é uma praga da cana-de-açúcar e outras plantações. O objetivo deste trabalho foi caracterizar variações morfológicas nas células epiteliais (colunares, caliciformes e regenerativas) ao longo do intestino médio de larvas de D. saccharalis. Fragmentos do intestino médio (anterior, mediano e posterior) foram fi xados e processados para microscopia de luz e eletrônica de varredura. Existem diferenças morfológicas citoquímicas e ultraestruturais nas células epiteliais, dependendo da sua localização no intestino médio. A superfície apical de algumas células colunares exibe projeções citoplasmáticas que aumentam em número e volume da região anterior para a posterior do intestino médio. Existe aumento dos grânulos PAS-positivos (Reação de Schiff) no citoplasma apical das células colunares e regenerativas, da região anterior para a posterior. A câmara das células caliciformes, na região anterior do intestino médio, mostra seu ápice estreito, enquanto que na posterior essa porção da câmara é alargada; as evaginações citoplasmáticas da câmara são pequenas e fi nas no ápice, sendo numerosas, longas e mais espessas na porção basal. Os resultados sugerem que o intestino médio da broca da cana apresenta duas regiões morfologicamente distintas, a anterior e posterior; a região mediana é uma região de transição.
Diferenças morfológicas regionais das células epiteliais ao longo do intestino médio de larvas de Diatraea saccharalis Fabricius (Lepidoptera: Crambidae)
Keywords: Histochemistry; Light microscopy; Morphology; Scanning electron microscopy; Sugarcane borer